Association between clinical findings and 3T MRI features in temporomandibular joint disorders - Şelale Özel; Selmi Tunç; Abdullah Utku Şenol (BMC Oral Health)
Abstract Background Temporomandibular joint disorders (TMD) commonly cause restricted mouth opening and pain, significantly affecting patients’ quality of life. This study aims to explore the relationship between common clinical symptoms—clicking and limited mouth opening—and MRI findings in patients diagnosed with TMD. Methods A total of 46 patients, with either clicking sounds or limited mouth opening, were examined using a 3T MRI scanner. The study evaluated disc position, disc deformity, and signs of osteoarthrosis, comparing MRI findings with clinical symptoms. Results Results revealed that disc deformation was positively correlated with clicking. In contrast, limited mouth opening was significantly associated with anterior disc displacement without reduction and osteoarthrosis, indicating joint degeneration. Conclusions The findings highlight that limited mouth opening is a more reliable clinical indicator of TMD than joint clicking, which may not always reflect underlying disc displacement. Although clicking was observed in discs with and without displacement, limited mouth opening showed a strong correlation with degenerative changes in the temporomandibular joint. The study underscores the reliability of clinical symptoms of TMD, which play a crucial role in treatment planing. Clinical trial number Not applicable.